Pengaruh Kontrol Diri dan Teman Sebaya Terhadap Motivasi Belajar Pada Mata Kuliah Manajemen Keuangan Mahasiswa Pendidikan Administrasi Perkantoran - Nadiya Rahmadina; Marsofiyati Marsofiyati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to analyze the effect of self-control and peers on student learning motivation in Financial Management courses in the Office Administration Education Study Program, State University of Jakarta. This research is motivated by the high dropout rate in Indonesia, which shows that learning motivation is an important factor in achieving academic success. The method used is quantitative with data analysis using the t test and F test to test the hypothesis. The results showed that self-control had no significant effect on learning motivation, with a t value of 1.455 and a significance of 0.170. In contrast, peer influence proved significant, with t count 2.640 and significance <0.001. The F test also showed that both variables simultaneously had a significant effect on learning motivation, with a calculated F value of 5.306 and significance below 0.05. The findings confirm the importance of social support from peers in increasing students' learning motivation, while self-control needs to be strengthened to support better academic achievement. This study provides recommendations for students to choose a positive social environment and for lecturers to create a learning atmosphere that supports interaction between students